2018
DOI: 10.3390/ma11030344
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Zinc and Phosphorus Elements Incorporated into Micro-Arc Oxidation Coatings Developed on Ti-6Al-4V Alloys

Abstract: In order to clarify the mechanism that zinc and phosphorus elements entering the micro-arc oxidation (MAO) coatings developed on Ti-6Al-4V alloys, anodic coatings containing different zinc and phosphorus were fabricated using an orthogonal experiment of four factors with three levels in an electrolyte containing EDTA-ZnNa2, KOH, and phytic acid. Surface morphology, element composition, chemical state and phase structure of MAO coatings were characterized by scanning electron microscope (SEM), energy dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…[71] Whereas, peak at 140.67 eV is corresponding to Zn 3s commonly arises in phosphorous chemical state in high resolution P 2p spectra of metal phosphides. [72] The high resolution spectra of C 1s are deconvolved into three peaks at 288.53, 286.30, and 284.69 eV corresponding to O─C═O, C─O─C, and C─C bonds, [8,73] respectively, in ZnP 2 @CoP-CNT/CC as shown in Figure 3d.…”
Section: Resultsmentioning
confidence: 99%
“…[71] Whereas, peak at 140.67 eV is corresponding to Zn 3s commonly arises in phosphorous chemical state in high resolution P 2p spectra of metal phosphides. [72] The high resolution spectra of C 1s are deconvolved into three peaks at 288.53, 286.30, and 284.69 eV corresponding to O─C═O, C─O─C, and C─C bonds, [8,73] respectively, in ZnP 2 @CoP-CNT/CC as shown in Figure 3d.…”
Section: Resultsmentioning
confidence: 99%
“…The integration of zinc onto titanium implant surfaces represents a trend in cationic surface modification, with the release of Zn 2+ significantly influencing bone integration. Zinc salts, such as zinc acetate, possess good water solubility, and a single MAO technique can be employed to immobilize zinc onto the surface coatings of titanium implants ( Hu et al, 2012 ; Du et al, 2018 ; Wang et al, 2018 ; Zhao et al, 2019b ; Komarova et al, 2020 ; Sun H. et al, 2022 ), as illustrated in Supplementary Table S2 .…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…In recent years, the fabrication of nano/micron coatings on the surface of titanium and its alloys has gained recognition as a means to enhance their biological attributes and boost their biological activity (van Hengel et al, 2021;Williams, 2022;Kuroda et al, 2023). Various techniques can be employed for creating these coatings, including hydrothermal treatment, physical vapor deposition, chemical vapor deposition, sol-gel methods, plasma immersion ion implantation, selective laser melting, plasma spraying, magnetron sputtering, and micro-arc oxidation (MAO) (Gu et al, 2004;Velasco-Ortega et al, 2010;Li et al, 2014;Wang et al, 2014;Kaluderovic et al, 2015;Zhang et al, 2015;Zhang Y. et al, 2018;Kaya et al, 2018;Kondyurin et al, 2018;Nichol et al, 2021;Bhatti et al, 2022;Sun Z. et al, 2022). However, these coating methods come with certain limitations (refer to Supplementary Table S1), such as reduced fatigue strength, degradation, and poor adhesion to the metal substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that diffusion and electromigration processes allowed calcium to enter, and the amount of phosphorus in the anode coating was strongly dependent on the amount of Ca(CH 3 COO) 2 . In the electrolyte containing EDTA-ZnNa 2 , KOH and phytic acid, the orthogonal experiment with four components and three levels was adopted to explore the influence of various technological factors on the amounts of Zn and P ( Wang Y. et al, 2018 ). The results showed that Zn entered the MAO membrane with P from phytic acid, and P mainly participated in membrane formation through diffusion.…”
Section: Electrolytementioning
confidence: 99%